2022
DOI: 10.3390/en15041499
|View full text |Cite
|
Sign up to set email alerts
|

Ash Behaviour during Combustion of Agropellets Produced by an Agro-Industry—Part 2: Chemical Characterization of Sintering and Deposition

Abstract: Eight different pellets (one woody and seven blends of woody and herbaceous biomass) produced by an agro-industry were tested in a fixed-bed reactor to characterize their behaviour during their combustion process. The objective was to analyze the possible problems that could arise and, thus, achieve advances in the greater penetration of these agropellets in the energy market. The blends’ design and tests results are presented in the first part of this article. The results of the bottom ash and fly ash samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…For these fuels, the sintering degree was lower (see Table ). As already verified in the tests carried out in the reactor and in other similar experiences, there is an inverse relationship between both values, due to sintering preventing entrainment, which, in turn, decreases inertial impact deposition. On the other hand, in the boiler test carried out with fuels of WSP family, the contribution of DR Cond.…”
Section: Experimental Test In a Commercial Grate Fired Boilersupporting
confidence: 74%
See 2 more Smart Citations
“…For these fuels, the sintering degree was lower (see Table ). As already verified in the tests carried out in the reactor and in other similar experiences, there is an inverse relationship between both values, due to sintering preventing entrainment, which, in turn, decreases inertial impact deposition. On the other hand, in the boiler test carried out with fuels of WSP family, the contribution of DR Cond.…”
Section: Experimental Test In a Commercial Grate Fired Boilersupporting
confidence: 74%
“…Regarding ash composition, the analysis of the results confirmed that neither the composition of fraction S1 or fraction S2/3 was related to λ, even in the WP100 in which the sintering degree did vary with this parameter. 33 Because a clear influence of λ on the sintering degree has not been found, except for the WP100, and the composition of each fraction was not affected by this parameter either, for the present analysis, it is interesting to work with mean values and an average composition (see Table 5). The sintering degree is much lower for WP100 than for the rest, and it increases as the percentage of herbaceous increases.…”
Section: Experimental Design and Test Featuresmentioning
confidence: 95%
See 1 more Smart Citation
“…Compared to plant-origin biomass, whose ash contents usually range from 0.37 to 10.44%, animal waste can be considered ash-rich [46]. Some types of conventional biomass feature ash content reaching 25% [47] nevertheless their thermal utilization may be associated with ash-related problems, such as deposition on heated surfaces and in flue gas ducts, and bed agglomeration in fluidized-bed combustion boilers (FBC) [48][49][50]. Therefore, the combustion of poultry litter may require the special design of the heat exchangers and dust collection equipment.…”
Section: Ash Contentmentioning
confidence: 99%
“…The results showed that the higher excess air ratio, the less condensation. In addition, the deposition of fly ash is related to the sintering of bottom ash . During sintering, the difference in ash behavior depends on its composition, especially Si, Ca + Mg, and K + Na.…”
Section: Introductionmentioning
confidence: 99%